Interfering Expression of Chimeric Transcript SEPT7P2-PSPH Promotes Cell Proliferation in Patients with Nasopharyngeal Carcinoma. (1st April 2019) - Wang, Jing; Xie, Guo-Feng; He, Yuan; Deng, Ling; Long, Ya-Kang; Yang, Xin-Hua; Ma, Jiang-Jun; Gong, Rui; Cen, Wen-Jian; Ye, Zu-Lu; Zeng, Yi-Xin; Wang, Hai-Yun; et al.
Abstract : Introduction . Nasopharyngeal carcinoma (NPC) is a distinct type of head and neck cancer which is mostly prevalent in southern China. The development of NPC involves accumulation of multiple genetic changes. Chromosomal translocation is always thought to be accompanied with the fusion chimeric products. To data, the role of the fusion chimeric transcript remains obscure. Materials and Methods . We performed RNA sequencing to detect the fusion genes in ten NPC tissues. Sanger sequencing and quantitative RT-PCR were used to measure the level of the fusion chimeric transcript in NPC tissues and cell lines. The functional experiments such as CCK8 assay, colony formation, and migration/invasion were conducted to analyze the role of this transcript in NPC in vitro . Results . We demonstrated that the chimeric transcript SEPT7P2-PSPH was formed by trans-splicing of adjacent genes in the absence of chromosomal rearrangement and observed in both NPC patients and cell lines in parallel. Low-expression of the SEPT7P2-PSPH chimeric transcript induced the protein expression of PSPH and promoted cell proliferation, metastasis/invasion, and transforming ability in vitro . Conclusions . Our findings indicate that the chimeric transcript SEPT7P2-PSPH is a product of trans-splicing of two adjacent genes and might be a tumor suppressor gene, potentially having the role of anticancer activity.